2020
DOI: 10.1080/15592324.2020.1755504
|View full text |Cite
|
Sign up to set email alerts
|

Lateral root development differs between main and secondary roots and depends on the ecotype

Abstract: Root architecture depends on the development of the main root and also on the number and density of lateral roots. Most molecular knowledge about the development of lateral roots was acquired studying primary roots, and it was implied that high order roots follow the same pattern. Recently, we informed that AtHB23 is differentially regulated in primary and secondary roots. Here we show that LBD16, a target of AtHB23, also is differentially regulated; it is expressed in the tip of secondary and tertiary roots b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…bp shorter than the one previously assessed (Perotti et al, 2019(Perotti et al, , 2020 and Fig. S1), our results suggest that the deleted region might include a repressor box.…”
Section: Statistical Analysessupporting
confidence: 41%
See 3 more Smart Citations
“…bp shorter than the one previously assessed (Perotti et al, 2019(Perotti et al, , 2020 and Fig. S1), our results suggest that the deleted region might include a repressor box.…”
Section: Statistical Analysessupporting
confidence: 41%
“…Previously, it was shown that in normal growth conditions, the knock-down of AtHB23 provoked an enhancement in LR initiation. This TF is upregulated by ARF7/19, induced the expression of LAX3 and repressed that of LBD16 in LR, and, importantly, this genetic program differed between second and third-order roots (Perotti et al, 2019(Perotti et al, , 2020. Under salinity stress, plants with altered levels of AtHB23 exhibited significant changes in root architecture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BD-HY5 + AD-STO and pDBLeu + pAD-502 were used as positive and negative controls, respectively. AtHB23ΔAHA: the C-terminal AHA domain was removed (Capella et al, 2014) AtMYB68 and AtPHL1 coexpress with AtHB23 in specific tissues and developmental stages of root development To test the functional sense of the interaction between these three TF, we first investigated the expression patterns of AtMYB68 and AtPHL1 in roots, the organ in which AtHB23 was deeply investigated, associated with developmental and salinity responses (Perotti et al, 2019(Perotti et al, , 2020(Perotti et al, , and 2022. For this purpose, we used 8-day-old transgenic plants carrying the constructs prAtMYB68:GUS and prAtPHL1:GUS.…”
mentioning
confidence: 99%